(untitled) (Journal of Student Affairs in Africa, 2021)
This special edition of Journal of Student Affairs in Africa (JSAA) represents an important milestone for South Africa’s First-Year Experience movement. This milestone is about reaching a particular stage of maturation in the drive to cultivate national First-Year Experience scholarship. It also shows the importance of the continued development of South Africa’s only dedicated national centre for First-Year Experience, i.e. the South African National Resource Centre for the First-Year Experience (SANRC), in terms of helping grow and nurture scholarship in the field.